Potential effects of endocrine-disrupting chemicals on preserved ratio impaired spirometry revealed by five different approaches - Chenyuan Deng; Yu Jiang; Yuechun Lin; Hengrui Liang; Wei Wang; Ying Huang; Jianxing He (Ecotoxicology and Environmental Safety, 2025)
Objective: Evidence from prior studies indicates that certain endocrine-disrupting chemicals (EDCs), such as phenols and phthalates, may serve as environmental risk factors for chronic obstructive pulmonary disease (COPD). However, no studies have examined the potential associations between EDCs and preserved ratio impaired spirometry (PRISm), a precursor to COPD. Methods: Data from 1363 participants in the NHANES 2007–2012 dataset were analyzed. Multiple logistic regression was employed to investigate the associations between individual EDCs and PRISm. The mixed effects of multiple EDCs on PRISm were assessed using three mixture analysis models: weighted quantile sum (WQS) regression, quantile g-computation (Qgcomp), and Bayesian kernel machine regression (BKMR). Additionally, the mediating roles of uric acid and SII were examined. Furthermore, an innovative identification model for PRISm was developed using participants’ demographic information and EDC exposure levels. Results: WQS regression and Qgcomp demonstrated that each index rise in the EDC-mixture index increased the odds of PRISm by 63 % (OR=1.63, 95 % CI: 1.25–2.13, P < 0.001) and 41 % (OR=1.41, 95 % CI: 1.15–1.72, P < 0.001), and BKMR model confirmed the same positive direction. The overall mixture effect was primarily attributable to mono-isobutyl phthalate (MIBP), which also yielded the largest single-chemical odds ratio in multivariable logistic regression (OR=2.29, 95 % CI: 1.71–3.07, P < 0.001). Mediation analysis showed that SII and uric acid mediated 15.8 % and 15.6 % of the association between mixed EDCs and PRISm, respectively. The results of SHAP interpretability analysis based CatBoost model further highlighted MIBP as the most informative environmental predictor. Conclusion: These findings suggest that exposure to EDCs may be linked to the prevalence of PRISm. These results provide novel epidemiological evidence for PRISm.